Older Adult Productive Activity Participation Using the National Health and Aging Trends Study. (March 2020) - Marfeo, Elizabeth E.; Ward, Caroline
This study aims to characterize factors related to productive activity participation among community-dwelling older adults. Cross-sectional analyses using data from the National Health and Aging Trends Study were used to calculate weighted frequencies representative of the U.S. population of older adults. Multivariate logistic regression was used to explore factors related to participation outcomes (paid work, volunteering, caregiving). We found that 21% of community-dwelling older adults in the United States reported currently working. Older adults reported working in a wide range of occupations. Driving emerged as one of the most important factors related to increased odds of productive activity participation. Age, gender, and health factors were also significantly associated with increased odds of productive activity participation. By understanding the current profile of participation in activities including employment, caregiving, and volunteering among a national sample of community-dwelling older adults, we can effectively inform intervention programs and resource allocation to support productive aging.